0321 Poor Agreement Among Self-Reported and Objective Sleep Deficiency Assessments in Older Persons. (25th May 2022) - Miner, Brienne; Yaggi, Henry; Gill, Thomas; Doyle, Margaret; Stone, Katie; Redline, Susan; Ensrud, Kristine; Blackwell, Terri; Knauert, Melissa
Abstract: Introduction: Many traditional sleep questionnaires were developed in younger populations and may have poor sensitivity to detect objective sleep deficiency in older persons due to atypical presentations, aging-related decreases in symptom awareness, and different expectations about health. Methods: In a secondary analysis of data from the Osteoporotic Fractures in Men (MrOS; Sleep Visit 1) and the Study of Osteoporotic Fractures (SOF Visit 9), we evaluated the prevalence of objective sleep deficiency among persons with scores in the normal range on traditional sleep questionnaires (Pittsburgh Sleep Quality Index [PSQI] <6 and Epworth Sleepiness Scale [ESS] <11). Objective sleep deficiency was established based on presence of sleep-disordered breathing (SDB; apnea hypopnea index [at >4% desaturation] per hour of sleep ≥15 on polysomnography), insufficient sleep duration (average sleep duration <6 hours on actigraphy), or impairment in daytime sustained attention/alertness (falling in the worst quartile of Digit Vigilance Test scores for the sex-specific cohort). Results: Average ages were 76±6 and 84±4 years in men and women, respectively. Among men with normal scores on the PSQI and ESS, 359/1527 (25%) had SDB, 428/1519 (28%) had insufficient sleep duration, and 346/1527 (23%) had impaired daytime attention/alertness. Among women with normal scores on both the PSQI and ESS, 72/185 (40%) had SDB, 318/1332 (24%) had insufficient sleep duration, and 140/546 (26%) had impaired daytime attention/alertness. Conclusion: A substantial proportion of older men and women with normal scores on traditional sleep questionnaires have objective sleep deficits, suggesting a need to develop instruments to improve detection of sleep deficiency in this population. Support (If Any): American Academy of Sleep Medicine Foundation, Yale Claude D. Pepper Older Americans Independence Center, Patterson Trust, National Institute on Aging